NATIONAL RESEARCH UNIVERSITY: SOCIAL AND TECHNOLOGICAL EXPERIENCE OF CREATION AND DEVELOPMENT - Leonid Ya. Dyatchenko (Высшее образование в России)
The paper highlights the Rector's experience in implementation of social and technological approach to management the processes of creation and development of a modern university. Figures and facts show the dynamics of its transformation from the provincial teacher training college to on one the leading national research universities. The applied approach included the participatory process, incorporation of human resources, development of the new forms of administration and management using the effective methods of social motivation. The keystone to success is a strict succession of the stages of the whole social and technological cycle implementation, coherent functioning of all subsystems, and a high accuracy of an every operation and action.